Analysis of gastric electrical rhythm in patients with type 2 diabetes mellitus - Wang, Xixi; Ma, Lianhua; Jiang, Miao; Zhu, Hong; Ni, Chendong; Yang, Xiaohua; Hu, Ji; Zhang, Hong-Hong (Endocrine, 2024)
Aim To analysis the change of electrogastrogram (EGG) in patients with type 2 diabetes mellitus (T2DM), and evaluate the prevalence of abnormal gastric electrical rhythm (AGER) and its relative influencing factors. Methods A total of 65 patients with T2DM hospitalized at the Second Affiliated Hospital of Soochow University from Dec. 2020 to Dec. 2021 were included in the cross-sectional study. General information, clinical data, and medical history data of all study subjects, including name, gender, body mass index (BMI), duration of diabetes, anti-diabetic therapies, high blood pressure (HBP) history, smoking history, and medication history, were completely collected. The results of laboratory tests, including biochemical parameters, glycosylated hemoglobin (HbA1c), fasting C-peptide, 2 h postprandial C-peptide, 24 h urine total protein (24 hUTP), urine microalbumin creatinine ratio (UACR) and estimated glomerular filtration rate (eGFR) were recorded. EGG, Gastroparesis Cardinal Symptom Index (GCSI), gastric emptying ultrasound, fundus examination, carotid artery ultrasonography, cardiac autonomic function test, heart rate variability (HRV) were all examined and recorded as well. According to the results of EGG, the subjects were divided into normal gastric electrical rhythm (NGER) group and abnormal gastric electrical rhythm (AGER) group. Results (1) Fasting blood glucose (FBG), HbA1c, the presence of diabetic peripheral neuropathy (DPN) and diabetic cardiac autonomic neuropathy (DCAN) were significantly higher in the AGER group ( p < 0.05). Low frequency (LF) and high frequency (HF), the indicators of HRV, were significantly lower in the AGER group ( p < 0.05). In addition, the prevalence of feeling excessively full after meals, loss of appetite, and stomach or belly visibly larger after meals of gastrointestinal symptoms of gastroparesis were significantly higher in the AGER group ( p < 0.05). Multiple logistic regression analysis showed that FBG and the prevalence of DCAN were the independent risk factors. Conclusion AGER was associated with high FBG and the presence of DCAN. EGG examination is recommended for patients with gastrointestinal symptoms and clues of DCAN.